A preparation method of magnetic metal organic framework material and its application in removing microplastics in food

By using the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al) to remove microplastics from food, it solves the problems of complex operations and high technical requirements of existing methods, and achieves efficient and simple removal of microplastics. And has good reuse performance.

CN116272878BActive Publication Date: 2025-01-21JIANGNAN UNIV

Patent Information

Application Number
CN202310113322.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-13
Publication Date
2025-01-21
Estimated Expiration
2043-02-13

AI Technical Summary

Technical Problem

The existing methods for removing microplastics are complex in operation and high technical requirements, and are limited to environmental background, and there is a lack of methods for removing microplastics in food.

Method used

The magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al) is used to remove microplastics in food through vibration and magnetic separation. The material preparation includes the synthesis of Fe3O4 magnetic microspheres, the synthesis of Fe3O4@SiO2 and Fe3O4@SiO2@MIL Synthesis of -53(Al).

Benefits of technology

It achieves efficient removal of various microplastics in food. The material can be recycled. It can still achieve 80% removal effect after being reused five times. The removal process is simple and has low technical requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116272878B_ABST
    Figure CN116272878B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method of a magnetic metal organic framework material and its application in removing microplastics in food, belonging to the field of food safety. The present invention uses drinking water, tea and wine as examples for explanation, and adsorbs and removes microplastics therein, so as to achieve a better effect of separating microplastics from food; the method based on the magnetic metal organic framework material can improve the efficiency and speed of removal, and reduce cumbersome operation steps such as centrifugation; and the method has a good removal effect. The method of the present invention can achieve the purpose of adsorbing and removing microplastics in food, and provides a theoretical and technical basis for the future control of microplastics in food.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of food safety, and specifically relates to a method for preparing a magnetic metal organic framework material and its application in removing microplastics in food. Background Art

[0002] Microplastics (MPs) are artificially synthesized solid particles or polymer matrices with regular or irregular shapes, size distribution may range from 1μm to 5mm, and are insoluble in water. Microplastics can be further classified into primary microplastics and secondary microplastics. Primary microplastics are produced directly by humans, such as personal care products and various cosmetics, which contain some microplastics to achieve a cleaning effect. Secondary microplastics are various plastic wastes discharged by humans, which are broken or degraded into micron-sized plastics due to the influence of the external environment (including but not limited to water flow, wind, sunlight, etc.). Due to the widespread use of plastic products in daily life and industrial production, microplastics have spread everywhere and have been detected in fresh water, oceans, soil and even air. Microplastics have been found even in polar regions that are difficult to reach.

[0003] Microplastics are so widely distributed in every corner of the world that humans are exposed to them unknowingly. There are three main ways of human exposure: ingestion, inhalation and direct contact. Researchers have therefore begun to evaluate and determine the hazards of microplastics. It is currently known that microplastics have no acute toxicity to humans, but they will accumulate in the human body. When they accumulate to a certain extent, they will have a subtle effect on the human body. In addition, not only will microplastics themselves have adverse effects on the human body, but various additives leaked from microplastics and persistent organic pollutants adsorbed on the surface of microplastics will also cause great harm and adverse effects. According to literature reports, microplastics can affect multiple systems of the human body, including the digestive system, respiratory system, nervous system and placental barrier. Harmful effects also include but are not limited to energy consumption, weight changes, inflammation, oxidative damage, etc.

[0004] Due to the hazards of microplastics themselves, understanding how to enrich, separate and remove microplastics has become a very important topic. Although some reports have tried to use various methods to remove microplastics, the application scenarios are still limited to environmental backgrounds. The current status of microplastics in food is also a problem that people are concerned about, and how to remove microplastics in food is still a blank area. Therefore, it is of great significance to establish a method to remove microplastics in food. Summary of the invention

[0005] [Technical issues]

[0006] Existing methods for removing microplastics are complex and highly technical, and are currently limited to food contexts. There is still a lack of methods for removing microplastics from food.

[0007] [Technical solution]

[0008] In order to solve at least one of the above problems, the present invention provides a method for removing microplastics in food based on magnetic metal-organic framework materials. The method of the present invention is simple to operate, does not have excessively high technical requirements, and can remove microplastics in food.

[0009] A method for preparing a magnetic metal organic framework material comprises the following steps:

[0010] (1) Synthesis of Fe3O4 magnetic microspheres: FeCl3·6H2O and anhydrous sodium acetate were placed in ethylene glycol and completely dissolved by ultrasonication. The dissolved solution was transferred to a reactor to react. After the reaction was completed, the product was cooled and washed with ethanol and water respectively. Then, the product was magnetically separated and dried to obtain magnetic microspheres Fe3O4.

[0011] (2) Synthesis of Fe3O4@SiO2: The magnetic microspheres Fe3O4 were ultrasonically washed in hydrochloric acid until the pH was neutral, then added to a mixed solution of water, anhydrous ethanol and ammonia solution and ultrasonicated, and tetraethyl orthosilicate was added and mechanically stirred. After the stirring was completed, the microspheres were washed with water and ethanol respectively until the pH was neutral, and then magnetically separated and dried to obtain Fe3O4@SiO2;

[0012] (3) Synthesis of Fe3O4@SiO2@MIL-53(Al): Fe3O4@SiO2, Al(NO3)3·9H2O and terephthalic acid were added to water and completely dissolved by ultrasonication. The dissolved solution was transferred to a reactor. After the reaction was completed and cooled, the solution was washed with water, N,N-dimethylformamide and ethanol respectively, and then magnetically separated and dried to obtain Fe3O4@SiO2@MIL-53(Al).

[0013] In one embodiment of the present invention, the mass ratio of FeCl3·6H2O to anhydrous sodium acetate in step (1) is 2.7:(5.5-6), and can be specifically 2.7:5.75.

[0014] In one embodiment of the present invention, the mass volume ratio of FeCl3·6H2O to ethylene glycol in step (1) is 2.7 g: (40-60) mL, and can be specifically 2.7 g: 50 mL.

[0015] In one embodiment of the present invention, the reaction conditions in the reactor in step (1) are a reaction temperature of 150-250° C. and a reaction time of 8 h.

[0016] In one embodiment of the present invention, the concentration of hydrochloric acid in step (2) is 0.1 mol / L; the volume mass ratio of hydrochloric acid to magnetic microspheres Fe3O4 is 200 mL: 1 g.

[0017] In one embodiment of the present invention, the washing in step (2) is performed until the pH value is 6.5 to 7.5.

[0018] In one embodiment of the present invention, in step (2), the mass volume ratio of the magnetic microspheres Fe3O4 and water is 1g:80mL; the mass volume ratio of the magnetic microspheres Fe3O4 and anhydrous ethanol is 1g:320mL; the volume ratio of the magnetic microspheres Fe3O4 and ammonia solution is 1g:5mL.

[0019] In one embodiment of the present invention, the mass concentration of the aqueous ammonia solution in step (2) is 25-28%.

[0020] In one embodiment of the present invention, the volume mass ratio of tetraethyl orthosilicate and magnetic microspheres Fe3O4 in step (2) is (0.5-1.5) mL:1 g, specifically 1 mL:1 g.

[0021] In one embodiment of the present invention, the mass ratio of Fe3O4@SiO2 and Al(NO3)3·9H2O in step (3) is 0.2:(1-1.5), and can be specifically 0.2:1.3.

[0022] In one embodiment of the present invention, in step (3), the mass ratio of Fe3O4@SiO2 to terephthalic acid is 0.2:(0.25-0.3), and can be specifically selected as 0.2:0.288.

[0023] In one embodiment of the present invention, the mass volume ratio of Fe3O4@SiO2 and water in step (3) is 0.2g:50mL.

[0024] In one embodiment of the present invention, the reaction conditions in the reactor in step (3) are a reaction temperature of 150-250° C. and a reaction time of 72 h.

[0025] A method for removing microplastics in food based on magnetic metal organic framework materials comprises the following steps:

[0026] The magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) of claim 1 is added to the food sample liquid and shaken, and after the shaking is completed, magnetic separation is performed.

[0027] In one embodiment of the present invention, the food sample liquid in the method for removing microplastics is drinking water, tea, coffee, white vinegar and wine, specifically drinking water, tea and wine.

[0028] In one embodiment of the present invention, the concentration of the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) added in the microplastic removal method is (0.05-0.15) mg / mL.

[0029] In one embodiment of the present invention, the shaking time in the method for removing microplastics is 15-30 minutes.

[0030] Beneficial effects of the present invention:

[0031] (1) The present invention uses magnetic metal-organic framework materials to effectively adsorb and remove various microplastics in the environment and food.

[0032] (2) The magnetic metal organic framework material used in the present invention can be recycled, and when the number of cycles reaches 5, the removal effect can still reach 80%.

[0033] (3) The method of the present invention can achieve the purpose of rapid removal of microplastics through magnetic metal-organic framework materials, and can reach a peak value within 15-30 minutes, providing a simple and quick removal method for the control and removal of microplastics in the environment and food. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope image of the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al).

[0035] Figure 2 This is the energy dispersive X-ray spectrum of the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al).

[0036] Figure 3 This is a transmission electron microscope image of the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al).

[0037] Figure 4 This is the Fourier infrared spectrum of the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al).

[0038] Figure 5 This is the X-ray diffraction spectrum of the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al).

[0039] Figure 6 This is the magnetic characterization diagram of the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al).

[0040] Figure 7This is a diagram showing the recycling performance of the magnetic metal-organic framework material Fe3O4@SiO2@MIL-53(Al). DETAILED DESCRIPTION

[0041] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0042] Example 1 Preparation of magnetic metal organic framework materials

[0043] (1) Synthesis of magnetic microspheres Fe3O4:

[0044] Weigh 2.7 g of FeCl3·6H2O and 5.75 g of anhydrous sodium acetate, dissolve them in 50 mL of ethylene glycol, and ultrasonicate for 30 min to completely dissolve them. Transfer the solution to a stainless steel reactor equipped with a polytetrafluoroethylene liner and react at 200°C for 8 h. After the reaction is completed and cooled to room temperature, wash the product in the reaction solution with ethanol and ultrapure water for 3-5 times, respectively, magnetically separate and dry overnight to obtain magnetic microspheres Fe3O4.

[0045] (2) Synthesis of Fe3O4@SiO2:

[0046] Weigh 1.0g of magnetic microspheres Fe3O4, ultrasonically treat it in 200mL of 0.1mol / L hydrochloric acid for 10min, wash it with ultrapure water to pH 7, then add it to a mixed solution of 80mL ultrapure water, 320mL anhydrous ethanol and 5mL ammonia solution (mass concentration 25-28%) for ultrasonic treatment for 15min, then add 1mL tetraethyl orthosilicate and stir mechanically for 12h. After stirring, wash the product in the reaction solution with ultrapure water and ethanol respectively to pH 7, magnetically separate and dry to obtain Fe3O4@SiO2.

[0047] (3) Synthesis of Fe3O4@SiO2@MIL-53(Al):

[0048] Weigh 0.2 g of Fe3O4@SiO2, 1.3 g of Al(NO3)3·9H2O and 0.288 g of terephthalic acid, add them into 50 mL of ultrapure water, and completely dissolve them by ultrasound. Transfer the solution to a stainless steel reactor equipped with a polytetrafluoroethylene liner, and react at 200°C for 72 h. After the reaction is completed and cooled to room temperature, wash the product in the reaction solution with ultrapure water, N,N-dimethylformamide and ethanol for 3-5 times, respectively, and magnetically separate and dry to obtain Fe3O4@SiO2@MIL-53(Al).

[0049] Example 2 Material Characterization

[0050] After the metal organic framework material Fe3O4@SiO2@MIL-53(Al) was synthesized, it was characterized by scanning electron microscopy (SEM), energy dispersive X-ray light (EDX), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and magnetism.

[0051] Respectively Figure 1-6 As shown, Figure 1 This is the SEM characterization image of Fe3O4@SiO2@MIL-53(Al), which proves that it is a spherical nanoparticle with a rough surface. Figure 2 This is the EDX curve of the obtained material, which proves that as the material is synthesized, its surface elements will increase accordingly. Finally, the curve of Fe3O4@SiO2@MIL-53(Al) contains elements such as Fe, C, O, and Al, proving the success of the material synthesis. Figure 3 This is the TEM characterization image of Fe3O4@SiO2@MIL-53(Al), which proves that the material has a core-shell structure. Figure 4 and Figure 5 It also helps determine the success of material synthesis by characterizing the bonds in the material and the crystal form, respectively. Figure 6 It is the magnetic characterization of the material. It can be seen that as the surface of the material is coated layer by layer, the magnetic properties of the material will decrease. This is a very normal phenomenon. In addition, the magnetic properties of Fe3O4@SiO2@MIL-53(Al) are also very good, meeting the needs of the experiment. All the results prove that the synthesized Fe3O4@SiO2@MIL-53(Al) is successful and has relatively good magnetic properties.

[0052] Example 3 Performance Testing

[0053] Testing process:

[0054] A glass beaker was selected as the container used for adsorption and removal, and its mass was weighed as m1. Fe3O4@SiO2@MIL-53(Al) and microplastic PVC (or PS, PP, PES) were weighed as m2 and m3 respectively and placed in a glass beaker, and m2:m3=10:1. Then 10 mL of solution was added, and the open mouth of the glass beaker was wrapped with tin foil. The glass beaker was then transferred to a shaker and shaken at 150 rpm for 30 min at 25°C.

[0055] After the shaking is finished, the magnetic separation is performed, and the water is dried, the total mass of the glass beaker and its contents is weighed again as m4. The removal effect can be calculated using the following formula.

[0056]

[0057] According to the adsorption performance tested in the above process, 1 mg of Fe3O4@SiO2@MIL-53(Al) and 10 mg of microplastic PVC were weighed, and then 10 mL of a mixed solution of ultrapure water and ethanol (v / v, 3:1) was added to simulate the existence and distribution of microplastics in the liquid natural environment. After calculation, it was found that in the case of a simulated liquid natural environment, the removal rate of PVC based on the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) can reach 93.17±4.20%, PS can reach 54.10±13.77%, PP can reach 85.16±1.59%, and PES can reach 88.28±11.81%.

[0058] Example 4 Removal of microplastics in drinking water

[0059] The 10 mL mixed solution of ultrapure water and ethanol (v / v, 3:1) in Example 3 was adjusted to 10 mL of drinking water, and the other contents were kept the same as in Example 3 for testing.

[0060] The test results are as follows: when the background is changed to drinking water, the removal rate of PVC based on the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) is 43.38±9.30%, PS is 18.28±15.08%, PP is 57.74±7.40%, and PES is 17.45±1.60%. Since ethanol is rich in hydroxyl groups and drinking water lacks hydroxyl groups, when microplastics exist in drinking water lacking hydroxyl groups, the microplastics will agglomerate and it is difficult to disperse evenly. This brings great difficulties to the adsorption and removal of microplastics by the magnetic material Fe3O4@SiO2@MIL-53(Al), resulting in a low adsorption rate, which is not as good as the removal effect in the simulated solution.

[0061] Example 5 Removal of microplastics in tea

[0062] The 10 mL mixed solution of ultrapure water and ethanol (v / v, 3:1) in Example 3 was adjusted to 10 mL of tea, and the other contents were kept the same as in Example 3 for testing.

[0063] The tea used is a certain brand of finished green tea, the main ingredients of which are water, green tea, vitamin C and sodium bicarbonate.

[0064] The test results are: when the background is changed to tea, the removal rate of PVC based on the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) is 88.99±12.60%, PS is 25.35±5.58%, PP is 63.26±7.91%, and PES is 69.13±8.15%.

[0065] Example 6 Removal of microplastics in wine

[0066] The 10 mL mixed solution of ultrapure water and ethanol (v / v, 3:1) in Example 3 was adjusted to 10 mL of wine, and the other contents were kept consistent with Example 3 for testing.

[0067] The liquor is a certain brand of gin with an alcohol content of 40% vol., and its main ingredients are water, juniper berries and wheat.

[0068] The test results are: when the background is changed to wine, the removal rate of PVC based on the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) is 97.10±1.21%, PS is 56.05±9.46%, PP is 94.67±3.18%, and PES is 82.74±6.15%.

[0069] Example 7 Repeated use performance test

[0070] Example 3 was adjusted. After the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) was used to adsorb and remove microplastics, the material was ultrasonically washed 3-5 times using tetrahydrofuran solution and anhydrous ethanol. The material was then dried overnight, and the operation in Example 3 was repeated with the material to measure the reusability of the material.

[0071] The test results show that after repeated use of the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) to adsorb and remove four types of microplastics, it was found that with the increase in the number of times, except for a certain degree of decline in the removal effect of PS, the removal effect of the other three materials only fluctuated slightly and basically remained above 80%. This proves that this material has very good stability and reusability.

[0072] Comparative Example 1

[0073] The shaking time in Example 3 was adjusted from 30 min to 60, 180, 360, 720, and 1440 min, and the other times were kept the same as in Example 1 for testing.

[0074] The test results show that as the oscillation time increases, the removal rate of microplastics based on the magnetic metal organic framework material Fe3O4@SiO2@MIL-53(Al) will also increase slightly, with almost no significant increase. At 30 minutes, the removal rate of PVC was 94.28±3.33%, the removal rate of PS was 31.48±13.98%, the removal rate of PP was 81.03±1.29%, and the removal rate of PES was 68.14±7.13%. In the time range of 60-1440min, the removal rate of PVC fluctuates from 90.94±3.00% to 96.46±0.58%, the removal rate of PS fluctuates from 23.89±10.20% to 54.10±13.77%, the removal rate of PP fluctuates from 78.25±3.39% to 85.16±1.59%, and the removal rate of PES fluctuates from 74.97±3.21% to 88.28±11.81%. The above data prove that when the oscillation time is 15-30min, the adsorption of microplastics by magnetic metal organic framework materials has basically reached saturation. Therefore, when it is in the dynamic equilibrium of adsorption, the adsorption increase will not be greater as time goes on. Considering the time cost, 15-30min can meet the requirements.

[0075] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the technology and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for removing microplastics in food based on magnetic metal organic framework materials, characterized in that: The steps include: Adding a magnetic metal organic framework material to a food sample solution and shaking it, and performing magnetic separation after the shaking is completed; the concentration of the added magnetic metal organic framework material is (0.05-0.15) mg / mL; the shaking time is 15-30 min; the food sample solution is drinking water, tea, coffee, white vinegar or wine; The method for preparing the magnetic metal organic framework material comprises the following steps: (1) Synthesis of Fe3O4 magnetic microspheres: FeCl3·6H2O and anhydrous sodium acetate were dissolved in ethylene glycol, and the dissolved solution was transferred to a reactor for reaction. After the reaction was completed, the product was cooled, separated, and washed, and then magnetically separated and dried to obtain magnetic microspheres Fe3O4; (2) Synthesis of Fe3O4@SiO2: The magnetic microspheres Fe3O4 were ultrasonically washed in hydrochloric acid until the pH was neutral, then added to a mixed solution of water, anhydrous ethanol and ammonia solution and ultrasonicated, and tetraethyl orthosilicate was added and stirred. After the stirring was completed, the mixture was washed until the pH was neutral, and then magnetically separated and dried to obtain Fe3O4@SiO2; (3) Synthesis of magnetic metal organic framework materials: Fe3O4@SiO2, Al(NO3)3·9H2O and terephthalic acid are dissolved in water, and the dissolved solution is transferred to a reactor for reaction. After the reaction is completed, the reaction is cooled, separated, washed, magnetically separated and dried to obtain a magnetic metal organic framework material; In step (1), the mass ratio of FeCl3·6H2O to anhydrous sodium acetate is 2.7: (5.5-6), and the mass volume ratio of FeCl3·6H2O to ethylene glycol is 2.7 g: (40-60) mL; In step (2), the concentration of hydrochloric acid is 0.1 mol / L, the volume mass ratio of hydrochloric acid to magnetic microspheres Fe3O4 is 200 mL: 1 g; the volume mass ratio of tetraethyl orthosilicate to magnetic microspheres Fe3O4 is (0.5-1.5) mL: 1 g; In step (3), the mass ratio of Fe3O4@SiO2 and Al(NO3)3·9H2O is 0.2:(1-1.5); the mass ratio of Fe3O4@SiO2 and terephthalic acid is 0.2:(0.25-0.3); the mass volume ratio of Fe3O4@SiO2 and water is 0.2 g:50 mL; the reaction conditions in the reactor are reaction temperature of 150-250°C and reaction time of 72 h.

Citation Information

Patent Citations

  • Magnetic MOFs solid phase extraction adsorbent as well as preparation method and application thereof

    CN105148853A

  • Method for simply and rapidly preparing high-price transition metal-based metal organic framework device in situ

    CN114452946A

Cited By

  • A method for separating microplastics in food or environment based on sustainable magnetic nanoparticles

    CN119926365B